Fire severity and changing composition of forest understory plant communities. (26th September 2019) - Stevens, Jens T.; Miller, Jesse E. D.; Fornwalt, Paula J.
Abstract: Questions: Gradients of fire severity in dry conifer forests can be associated with variation in understory floristic composition. Recent work in dry conifer forests in California, USA, has suggested that more severely burned stands contain more thermophilic taxa (those associated with warmer and drier conditions), and that forest disturbance may therefore accelerate floristic shifts already underway due to climate change. However, it remains unknown how rapidly thermophilic taxa shifts occur following disturbance, how long such shifts are likely to persist, and how different thermophilic post‐disturbance communities are from pre‐disturbance communities. Location: Colorado Front Range, USA. Methods: We investigated these questions using a unique 15‐year vegetation plot dataset that captures pre‐ and post‐fire understory community composition across a gradient of fire severity in dry conifer forests, classifying taxa using the biogeographic affinity concept. Results: Thermophilization (defined here as a decrease in the ratio of cool‐mesic taxa to warm‐xeric taxa, based on biogeographic affinity of paleobotanical lineages) was observed as early as one year post‐fire for all fire severity classes, but was stronger at sites that burned at higher severity. The ratio of cool‐mesic to warm‐xeric taxa recovered to pre‐fire levels within 10 years in stands that burned at low severity, but not in stands that burned at moderate or high severity. The process of thermophilization after high‐severity fire appears to be driven primarily by the gain of warm‐xeric taxa that were absent before the fire, but losses of cool‐mesic taxa, which did not return during the duration of the study, also played a role. Conclusions: Decreases in canopy cover appear to be a main contributor to understory thermophilization. Fine‐scale heterogeneity in post‐fire forest structure is likely an important driver of floristic diversity, creating the microclimatic variation necessary to maintain floristic refugia for species mal‐adapted to increasingly warm and dry conditions. Abstract : Forest fire can cause understory vegetation to experience warmer and drier microclimates by removing forest canopy. This paper uses a unique pre‐ and post‐fire floristic dataset from Colorado, USA, to document a post‐fire shift towards understory plant taxa with affinities for warmer and drier conditions, which is more pronounced at increasing levels of canopy loss.